2009
DOI: 10.1007/s11251-009-9110-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load theory, educational research, and instructional design: some food for thought

Abstract: Cognitive load is a theoretical notion with an increasingly central role in the educational research literature. The basic idea of cognitive load theory is that cognitive capacity in working memory is limited, so that if a learning task requires too much capacity, learning will be hampered. The recommended remedy is to design instructional systems that optimize the use of working memory capacity and avoid cognitive overload. Cognitive load theory has advanced educational research considerably and has been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
574
0
25

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 769 publications
(607 citation statements)
references
References 183 publications
8
574
0
25
Order By: Relevance
“…Therefore, the demands of the task are reduced, which is likely to support goal-directed remembering (de Jong, 2010), while simultaneously providing retrieval support in line with the Task Support Hypothesis (Bowler et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the demands of the task are reduced, which is likely to support goal-directed remembering (de Jong, 2010), while simultaneously providing retrieval support in line with the Task Support Hypothesis (Bowler et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Taken together with previous pilot studies [40], knowledge maps has demonstrated high usability and accessibility. These are essential qualities for any educational tool, particularly if it is to be used for assessment purposes [50,51]. The large loss of subjects for the survey, with a 25% completion rate, is a potential source of bias.…”
Section: Discussionmentioning
confidence: 99%
“…We mined Web logs to discover students' learning task completion times in the anchored discussion system. Since students' post-test scores related to the learning task, we used posttest scores as a direct measurement of their performance (for a similar approach, see De Jong, 2010). We then standardized the pre-and post-test scores because they used different scoring scales.…”
Section: Learning Efficiencymentioning
confidence: 99%